MIGRATIONS : Wildlife in motion - Wolfe, Art; Sleeper, Barbara (San Rafael, California : Earth Aware Editions,|c2016., 2016)
Inspired by the imaginative spatial designs of Dutch artist M.C. Escher, photographer Art Wolfe traveled the globe in search of similar patterns in nature. The result is a book of remarkable wildlife images that captures both the beauty and the poignancy of animals on the move. Migrations draws the reader into the energy, motion, and enduring spirit of life on this planet. The stunning images capture the delicate balance of our ecosystem, conveying the primordial stirrings that prompt a flock of snow geese to head south, monarch butterflies to bejewel a forest of trees, or a colony of Indian bats to snuggle in tight hibernation, while also serving as a telling reminder of life's fragility. It carries a message of both celebration and conservation. Kenya, Japan, South Georgia Island, Trinidad, the Canadian Arctic, and the Ozarks are among the locations that create the backdrop for Wolfe's dramatic artistry as he showcases "classic migrations," the beauty of their trek, the splendor of the patterns they create, and the cycles they are compelled to repeat.
Previous edition: 1994.
Keywords: Animal migration -- Pictorial works; Animals -- Pictorial works; Photobooks